UNLOCKING DIGITAL BANKING ADOPTION: THE ROLE OF EASE OF USE, SECURITY, AND TRUST IN GENERATION Z - Sukri, Nely Novia; Azar, Moh Azus Shony; Shoimah, Siti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to examine the influence of perceived ease of use, security, and trust on the interest in using digital banking among Generation Z in Lamongan Regency. This research was conducted among Generation Z in Lamongan Regency. This study used quantitative research. The population in this study was Generation Z in Lamongan Regency. Sampling used the Slovin formula, resulting in a sample of 100 respondents. The data collection technique used a questionnaire. From the results of the analysis, there are t-test results for the perceived ease of use variable greater than the t-table value (3,802 > 1.98498) and a significance value of (0.000 < 0.05), so that Perceived Ease Of Use has a positive and significant effect on Intention to Use, the t-test results of the security variable t count and t table are (8.345 > 1.98498) and a significance value of (0.000 < 0.05), so it can be concluded that Security has a positive and significant effect on Intention to Use, the t count and t table values on the perceived trust variable are (3.593 > 1.98498) and a significance value of (0.001 < 0.05), so it can be concluded that Perceived Trust has a positive and significant effect on Intention to Use. While the adjusted R square value is 0.800 or 80%. This indicates that the variable of Intention to Use (Y) that can be influenced by the variables Perceived Ease of Use, Security, and Perceived Trust is 80%. Meanwhile, the remaining 0.200 or 20% is influenced by other variables not examined in this study   Keywords: Perceived Ease of Use, Security, Perceived Trust and Interest in Use